MRI radiomics and potential applications to glioblastoma - Hooper, Grayson W.; Ginat, Daniel T. (Frontiers in Oncology, 2023)
MRI plays an important role in the evaluation of glioblastoma, both at initial diagnosis and follow up after treatment. Quantitative analysis via radiomics can potentially augment the interpretation of MRI in terms of providing insights regarding the differential diagnosis, genotype, treatment response, and prognosis. The various MRI radiomic features of glioblastoma and their clinical implications are reviewed in this article.